Transient receptor potential melastatin 2 regulates neutrophil extracellular traps formation and delays resolution of neutrophil-driven sterile inflammation - Xue Cao; Yanhong Li; Yubin Luo; Tianshu Chu; Hang Yang; Ji Wen; Yi Liu; Yi Zhao; Martin Herrmann (BMC, 2023)
Abstract The formation of neutrophil extracellular traps (NETs) is a process releasing into the extracellular space networks of chromatin fibers decorated with granular proteins. It is implicated in infection-related as well as sterile inflammation. Monosodium urate (MSU) crystals serve as damage-associated molecular pattern (DAMP) in various conditions of disease. Formation of NETs or aggregated NETs (aggNETs) orchestrates initiation and resolution of MSU crystals-triggered inflammation, respectively. Elevated intracellular calcium levels and the generation of reactive oxygen species (ROS) are crucial for the formation of MSU crystal-induced NETs. However, the exact signaling pathways involved are still elusive. Herein, we demonstrate that the ROS-sensing, non-selective calcium-permeable channel transient receptor potential cation channel subfamily M member 2 (TRPM2) is required for a full-blown MSU crystal-induced NET formation. Primary neutrophils from TRPM2−/− mice showed reduced calcium influx and ROS production and, consequently a reduced formation of MSU crystal-induced NETs and aggNETs. Furthermore, in TRPM2−/− mice the infiltration of inflammatory cells into infected tissues and their production of inflammatory mediators was suppressed. Taken together these results describe an inflammatory role of TRPM2 for neutrophil-driven inflammation and identify TRPM2 as potential target for therapeutic intervention.